Clinical characteristics of patients with anti-TIF1-γ antibodies - Anna Masiak; Julia Kulczycka; Zenobia Czuszyńska; Zbigniew Zdrojewski (Rheumatology, 2016)
Objectives : Inflammatory myopathies are a group of idiopathic, heterogeneous systemic diseases affecting predominantly skeletal muscles, though they can also involve the skin and internal organs. The association between cancer and idiopathic inflammatory myopathies, particularly dermatomyositis, which is termed cancer-associated myositis (CAM), has been reported in the medical literature. A newly described autoantibody to a 155-kDa nuclear protein, identified as transcription intermediary factor 1-gamma (TIF1-γ), has proven useful for cancer screening in patients with dermatomyositis. Material and methods: Based on our database of laboratory results, between November 2014 and January 2016, we found 80 patients with a positive autoimmune inflammatory myopathy immunoblot profile. Results : Eleven of 80 patients revealed the presence of anti-TIF1-γ antibodies: 8 women and 3 men with average age 54.2 years. Dermatomyositis (DM) was diagnosed in 6 cases, polymyositis in 1 case, myositis limited to ocular muscles and rhabdomyolysis in 1 case each, and undifferentiated connective tissue disease in 2 cases. Neoplasm was found in 4 cases. All of those patients had DM. The average time between DM and diagnosis of neoplasm was 7.5 months (from 1 to 18 months). Conclusions : The association between cancer and idiopathic inflammatory myopathies, particularly DM, is well known, and cancer screening should be obligatory in such patients. So far there is no consensus as to the method or frequency with which patients with an idiopathic inflammatory myopathy should be tested to rule out neoplasm. Detection of anti-TIF1-γ antibodies in patients with DM gives the clinicians the very important suggestion of CAM. It seems reasonable that these patients should have more detailed and often repeated differential diagnostics.